PENGARUH SUHU PEMBAKARAN TERHADAP KARAKTERISTIK LISTRIK KERAMIK FILM TEBAL BERBASIS Fe2O3-MnO-ZnO UNTUK TERMISTOR NTC - Sari, Puspita (2016)
Pembuatan keramik film tebal berbasis Fe2O3-MnO-ZnO untuk termistor NTC dari campuran Fe2O3 50%mol, MnO 25%mol, dan ZnO 25%moltelahdilakukan.Campuranserbuk Fe2O3, MnOdanZnO yang telahdigerusdicampurkandenganorganic vehicle (OV) untukmembentuk pasta.Kemudian pasta dilapiskan di atassubstrat alumina menggunakanteknikscreen printing untukmembentuk film tebal. Film tebalmentah yang diperoleh, dibakarpadasuhu yang berbedayaitu 1000°C, 1100°C, dan 1200°C selama 2 jam. Sebelumdilakukanpengukuranresistansi, film tebaldilapisiperakterlebihdahulusebagaikontaklogam.Resistansitermistordiukurpadasuhu 40°C-200 oCdenganbedasuhusebesar 5 oC.Analisisstrukturkristaldanstrukturmikro film tebalmasing - masingdilakukandenganmenggunakanX - Ray Diffraction(XRD) danScanning Electron Microscopy (SEM). Hasilanalisiskarakteristiklistriktermistoryang dibakarpadasuhu 1000 °C, 1100 °C, dan 1200 °C menghasilkankonstantatermistorberturut - turutsebesar7700 K, 6995 K, dan 5701 K. Ketigasuhupembakaranmenghasilkannilaikonstantatermistor yang memenuhikebutuhanpasar. AnalisisstrukturkristalmenggunakanXRDmenunjukkanbahwakeramik film tebalmemilikiduastrukturyaitustrukturspinel kubikdanhematitheksagonal. AnalisisstrukturmikromenggunakanSEMmenunjukkanbertambahnyaukuranbutirsesuaidenganmeningkatnyasuhupembakarandenganukuranbutir film tebal yang dibakarpadasuhu 1000 °C, 1100 °C, dan 1200 °Cberturut - turutadalah 1.3 μm, 2.0 μm, dan 2.4 μm.;--- Fabrication of thick film based on Fe2O3-MnO-ZnOfor NTC thermistor made from a mixture Fe2O3 50% mol, MnO 25% mol, and ZnO 25% mol has been done. The powder mixture Fe2O3, MnO, and ZnO that has been grinded was mixed with organic vehicle (OV) to form a paste. Then the paste was coated on the alumina substrat using screen printing technique to form a thick film. The crude thick film were burned at different temperatures are 1000°C, 1100°C, and 1200°C for 2 hours. Before resistance was measurement, the thick films were coated with Ag as the metal contact. The thermistor resistance was measured at 40°C-200 oC with increasement temperature 5 oC.The analysis of crystal structure and microstructure of each thick film done using X - Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). According to the electrical resistant measurement data, the thermistors constant of the samples burned at 1000°C, 1100°C, and 1200°C were 7700 K, 6995 K, and 5701 K respectively. The thermistor constant of all samples met the market requirement. The crystal structure analysis data showed that the thick films possessed two crystal structure namely cubic spinel and hematite hexagonal. The microstructure analysis using SEM showed an increase in grain size following to the firing temperature increase. The grain size of the thick film that were burned at 1000 °C, 1100 °C, and 1200 °C were 1.3 μm, 2.0 μm, and 2.4 μm respectively.